PENGARUH PENERAPAN STRATEGI AKTIF TIPE BERBAGI PENGETAHUAN SECARA AKTIF TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 17 PADANG - Mulki, Fadhillah - (STKIP PGRI Sumbar, 2014)
This research was motivated by student who cannot share their knowledge well and lack of comprehension of mathematical concept. The purpose of this research is to know about does Active knowledge sharing strategy influential toward studentâs comprehension mathematical concept. Kind of this research is pre-experiment by pre-test and post-test group design. Population in this research is junior high school studentâs class VIII of SMPN 17 Padang on academic year 2014/ 2015 that consist of seven classes. Technique sample of this research is random sampling, the sample is VIII4 class. The instrument in this research is comprehension mathematical concept test, that is pre-test and post-test with essay questions. Technique analysis data in this research use uji- and get and with, so and can concluded that there is influence of Active Knowledge sharing strategy toward studentâs comprehension mathematical concept class VIII of SMPN 17 Padang.